Case report: Histoplasmosis presenting as asymptomatic hypercalcemia detected on routine laboratory testing in a pediatric kidney transplant recipient - Spiwak, Elizabeth; Goswami, Shrea; Lay, Sara E.; Nailescu, Corina (Frontiers in Pediatrics, 2023)
Among all infections occurring in pediatric kidney transplant recipients, approximately 1%–5% are fungal. Most fungal infections occur in the first 6 months following kidney transplantation. We present the case of a 15-year-old boy with a history of a kidney transplant 4 years ago, who was found to have asymptomatic moderate hypercalcemia on routine laboratory testing, along with an acute deterioration of his kidney function markers. The cause of his acute kidney injury was likely related to hypercalcemia. An extensive workup for hypercalcemia revealed infection with Histoplasma capsulatum (histoplasmosis) with multiple pulmonary nodules. Hypercalcemia that was initially refractory to medical management resolved after initiating the antifungal treatment. Fungal granulomatous infections such as histoplasmosis should be considered in the differential diagnosis of hypercalcemia in an asymptomatic pediatric kidney transplant recipient.